2014
DOI: 10.1111/jam.12458
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the tea catechin epigallocatechin gallate on Porphyromonas gingivalis biofilms

Abstract: Aims: The aim of this study was to investigate the effects of tea catechin epigallocatechin gallate (EGCg) on established biofilms and biofilm formation by Porphyromonas gingivalis, a major pathogen of periodontal disease. Methods and Results: Biofilm cell survival was measured using adenosine triphosphate (ATP) bioluminescence. In the presence of EGCg, the ATP level in cells of established biofilms was significantly decreased compared to the controls (P < 0Á0001). Transmission electron microscopy revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 33 publications
(56 reference statements)
2
53
0
13
Order By: Relevance
“…Calculus formation is the result of petrification of dental plaque biofilm, with mineral ions provided by bathing saliva or crevicular fluids [10]. Supragingival calculus formation can be controlled by chemical mineralization inhibitors, applied in toothpastes or mouth rinses [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Calculus formation is the result of petrification of dental plaque biofilm, with mineral ions provided by bathing saliva or crevicular fluids [10]. Supragingival calculus formation can be controlled by chemical mineralization inhibitors, applied in toothpastes or mouth rinses [11].…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm cell survival can be measured using the ATP-driven bioluminescence [10]. Using the luciferin substrate and luciferase enzyme, bacterial ATP can be quantified by measuring the release of visible light.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell concentrations were adjusted to 0.5 McFarland turbidity standards (equivalent to 1.5×10 8 colony forming units/ mL). Thereafter, Porphyromonas gingivalis was treated with various CAPAJ parameters and bacterial surface morphology was studied using SEM 41) . Concurrently, changes occurring on titanium specimen roughness after treatment of CAPAJ were observed.…”
Section: Porphyromonas Gingivalis and Titanium Specimen Surface Sem Amentioning
confidence: 99%
“…In the field of dentistry, it has also been reported that sub-MICs of antimicrobial agents or compounds can inhibit bacterial attachment [54,56,57], biofilm formation [54,55,57,58], and downregulate virulence genes [54,56,59,60]. Moon et al reported N-acetyl cysteine (NAC) that is an antioxidant possessing anti-inflammatory activities, showed a significant decrease of Prevotella intermedia biofilm formation in the presence of sub-MIC [55].…”
Section: Antimicrobials-induced Biofilm Formationmentioning
confidence: 99%